2019
DOI: 10.1017/jfm.2019.282
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational convection in a heterogeneous binary mixture. Part 1. Time-averaged equations

Abstract: High-frequency vibrations of a container filled with a fluid generate pulsation flows that however are barely visible with the naked eye, and induce the slow but large-amplitude averaged flows that are important for various practical applications. In this work we derive a theoretical model that gives the averaged description of the influence of uniform high-frequency vibrations on an isothermal mixture of two slowly miscible liquids. The miscible multiphase system is described within the framework of the phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…In addition to the acceleration amplitude, the imposed ∆T, and the aforementioned angle Θ, an additional degree of freedom influencing the dynamics is represented by the 'frequency' of vibrations. Nevertheless, only a limited number of studies are available in the literature where this variant of buoyancy flow was considered (Monti et al [8]; Alexander [9]; Alexander et al [10,11]; Feonychev and Dolgikh [12]; Gershuni and Lyubimov [13]; Monti et al [14]; Naumann [15]; Mialdun et al [16]; Melnikov et al [17]; Lyubimova et al [18]; Bouarab et al [19]; Shevtsova et al [20,21]; Maryshev et al [22]; Vorobev and Lyubimova [23]; Lappa, [24][25][26][27][28]; Lappa and Burel [29]). Still fewer articles have been devoted to the case where vibrations and temperature gradient are parallel.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the acceleration amplitude, the imposed ∆T, and the aforementioned angle Θ, an additional degree of freedom influencing the dynamics is represented by the 'frequency' of vibrations. Nevertheless, only a limited number of studies are available in the literature where this variant of buoyancy flow was considered (Monti et al [8]; Alexander [9]; Alexander et al [10,11]; Feonychev and Dolgikh [12]; Gershuni and Lyubimov [13]; Monti et al [14]; Naumann [15]; Mialdun et al [16]; Melnikov et al [17]; Lyubimova et al [18]; Bouarab et al [19]; Shevtsova et al [20,21]; Maryshev et al [22]; Vorobev and Lyubimova [23]; Lappa, [24][25][26][27][28]; Lappa and Burel [29]). Still fewer articles have been devoted to the case where vibrations and temperature gradient are parallel.…”
Section: Introductionmentioning
confidence: 99%
“…When a fluid is shaken in the presence of an imposed temperature difference, the emerging flow is known as thermovibrational convection (Gershuni and Lyubimov 44 ; Mialdun et al, 45 ; Lyubimova 46 ; Bourab et al, 47 ; Shevtsova et al, 48,49 , Maryshev et al, 50 ; Lappa 51 ; Vorobev and Lyubimova 52 ).…”
Section: Introductionmentioning
confidence: 99%
“…The full equations are however too hard for direct numerical simulations, as these equations include the full continuity equation (that is called the effect of quasi-compressibility and that is explained by the dependence of the mixture density on concentration). It was later shown that the slower convective and diffusive evolution of a mixture can be determined on the basis of the fully incompressible equations, that represent the Boussinesq approximation of the full Cahn-Hilliard-Navier-Stokes equations [29,30]. The Boussinesq approximation of the Cahn-Hilliard-Navier-Stokes equations are numerically solved in the current work to describe the evolution of a heterogeneous binary mixture.…”
Section: Mathematical Modelmentioning
confidence: 99%